Pengaruh kualitas layanan terhadap loyalitas pelanggan dengan kepuasan pelanggan sebagai variabel intervening - Rita Zahara (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2020)
This study aims to determine whether the direct effect of service quality on loyalty and indirect influence through customer satisfaction. This type of research is a quantitative associative that discusses the influence of service quality on customer loyalty with customer satisfaction as an intervening variable. The object of research is the users of Gojek service applications during the period of October 2018 to August 2019. The path analysis technique is used to test the hypothesis. The results showed that service quality has an influence on customer satisfaction and customer loyalty, but satisfaction does not significantly affect loyalty so that the indirect relationship between quality and loyalty through customer satisfaction cannot be verified. Implications and suggestions are explained in the article.